PERANCANGAN BOT UNTUK MONITORING SERVER DARI SERANGAN DISTRIBUTED DENIAL OF SERVICE MENGGUNAKAN JSON WEB TOKEN - Arif Maulana Rahman (2020)
In running a server, a monitoring system is needed to secure the network in order to minimize the risk if an intrusion attempt occurs. One of the attacks that often occurs to servers is a DDOS (Distributed Denial of Service) attack which results in the system being attacked experiencing interference in the form of error requests, halt, system failure and so on. Based on the problems described, a bot is needed to monitor and protect the server from DDOS attacks, in this study the focus is on DDOS attacks of the UDP Flooding and SYN Flooding types. This bot will be able to detect UDP Flooding and SYN Flooding attacks by limiting the number of packets addressed to the port opened by the server, if the bot detects an attack the bot will block and send notifications to the server admin by implementing push notification sets and using JSON Web Tokens to ensure The integrity and confidentiality of notifications sent by the bot to the server admin smartphone are maintained. Server monitoring makes use of bot to detect DDOS attacks of the UDP Flooding and SYN Flooding types by limiting the number of packets sent to the port opened by the server, if the number of packets sent is more than 100 packets per second, the bot will identify the sending as an attack. The application of the JSON Web Token method so that it can be operated by the server admin bot, namely by implementing the JSON Web Token package on the bot and then calling the encode function so that the JSON Web Token can encrypt claims containing attacker data by bot, so that the admin server bot can secure claims that will sent to the server admin.